Early Child Education : Making Programs Work for Brazil’s Most Important Generation - Evans, David K.; Kosec, Katrina (Washington, DC: World Bank, 2013)
This report draws deeply on the extraordinary efforts and innovations demonstrated by early child development policy makers around Brazil. This report draws on background papers about innovations in early child education in Rio de Janeiro and in caregiver training and supervision in two municipalities within Sao Paulo state. The year 2011 marked the beginning of a new administration in Brazil. The Ministry of education clearly identified early child education (ECE) as one of the top priorities of the new administration, along with secondary school and improving the reputation of the teaching profession. Early child development interventions are essential to both increasing the productivity of Brazil as a whole and to providing equitable opportunities for the disadvantaged. These programs benefit the poor more than other populations, and the poor are most in need of these benefits. Education interventions are crucial. Creches and preschools provide opportunities for stimulation and development that can wire children for future success. Therefore, early child education can particularly benefit the poor, helping to close the gap in cognitive development across income groups. A World Bank study compares adults from two regions of Brazil (the Northeast and the Southeast) who attended preschool to those who did not and found that pre-school attendance is associated with additional total years of education.